Sosialisasi Pengenalan Dunia Kampus Menyongsong Impian Siswa Di SMAN 8, SMAS Pertiwi 1, SMAS Pertiwi 2 Dan SMAS Pembangunan Labor UNP Kota Padang Provinsi Sumatera Barat - Rosa, Yenni Del; Putri, Siska Lusia; Yan Fitri, Mellyna Eka; Abdilla, Mohammad; Yendra, Nofri; Riski, Tri Rachmat; Mawadah, Aulia; Kamila, Zahra (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
There are several percent of grade XII high school students in Padang city who do not understand the importance of studying at university and the constraints of tuition fees for those who are less fortunate. This has an impact on the relatively low mindset for the intelligence of the nation in the future. The purpose of community service activities is to increase the number of grade XII high school graduates in Padang city with scholarships accepted at State Universities every year. The method of implementing activities according to priority problems with the solutions offered in the form of lectures, discussions and counseling methods. The solution offered to grade XII high school students in Padang city provides counseling on the importance of studying at university and scholarships for those who are less financially able. This solution is expected to have an impact on the number of high school graduates in Padang city accepted at State Universities every year increasing by around more than 80%. Continuing education to university is very important because it can increase knowledge and skills, open up career opportunities and develop personality. To continue their education, prospective students can obtain various types of scholarships provided by the government and the private sector.